2020
DOI: 10.31124/advance.13356866.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What motivates the most? Money or Empowerment: Mediating Role of Employee Commitment to Organizational Performance

Abstract: A structured questionnaire was used to collect data on HR practices, employee commitment, and organizational performance. Data was collected from the 759 employees of the industrial sector in Saudi Arabia.<br>

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Furthermore, various other studies have demonstrated that teacher enthusiasm and empowerment are also mediated by teacher commitment, thus exerting a positive influence on teacher organizational behavior (Cheasakul & Varma, 2015). In the context of the business world, research has also been conducted, the findings of which revealed that commitment can serve as a mediating variable of empowerment, even in the industrial sector (Akhtar et al, 2020).…”
Section: Revised Amendments From Versionmentioning
confidence: 99%
“…Furthermore, various other studies have demonstrated that teacher enthusiasm and empowerment are also mediated by teacher commitment, thus exerting a positive influence on teacher organizational behavior (Cheasakul & Varma, 2015). In the context of the business world, research has also been conducted, the findings of which revealed that commitment can serve as a mediating variable of empowerment, even in the industrial sector (Akhtar et al, 2020).…”
Section: Revised Amendments From Versionmentioning
confidence: 99%